Bio Functional Evaluation of EGFR Expression as a Prognostic Indicator in Oral Squamous Cell Carcinoma and a Recommendation for Personalized Targeted Therapy with Anti EGFR Inhibitors - Karthikeya Patil; Jayashree K; Mahima V Guledgud; Aishwarya R; Prasannasrinivas Deshpande; Nagabhushana Doggalli (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Carcinoma is a complex, multifactorial and a devastating disease. Understanding the molecularchanges that leads to disease enables one to develop strategies to prevent, provide an early diagnosis andserve as targets for therapy. Epidermal Growth Factor Receptor (EGFR), a 170-kDa cell-surface proteinis a tyrosine kinase receptor from the ErbB family and is involved in many biological processes thataffect tumour development, growth progression, differentiation, inhibition of apoptosis and developmentof metastasis. Methods: Study included 54 cases of oral squamous cell carcinomas. EGFR expression byimmunohistochemistry has been studied, correlated with clinical parameters, known prognostic factors andpatient survival to note its significance.Conclusion: Head and Neck Squamous Cell Carcinoma (HNSCC) with or without regional lymph nodemetastases, are challenging to treat effectively. The prognosis for the patients with advanced stage of thedisease still remains poor. The correlation of EGFR overexpression with tumour size, grade, stage andsurvival suggests that EGFR expression can be considered as having prognostic significance and is apotential target for therapy with EGFR inhibitors in HNSCC. Further studies are required to assure theviability of EGFR levels in saliva as non-invasive prognostic marker and also as an indicator of recurrence.